2020
DOI: 10.1155/2020/2478579
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Method of Specific Surface Area of Foam Metal Based on an Ideal Tetradecahedron Model for Lithium Ion Battery

Abstract: A novel calculation method of specific surface area of tetrahedral foam metal is established. The expressions of the two basic parameters of the foam metal with respect to porosity and pore size are derived by using the geometrical relationship of this model; consequently, the specific surface area of the metal foam is easily calculated. The theoretical calculation data are compared with the experimental results; it shows that the specific surface area of various porous metals, such as nickel foam and copper f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…More accurate models can be found in literature data for calculation of the geometric surface of metal foams but we will keep A g = 40 cm 2 cm −3 as the order of magnitude for the present study. 18 Thus, the geometric surface area of a piece of nickel foam electrode can be calculated by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…More accurate models can be found in literature data for calculation of the geometric surface of metal foams but we will keep A g = 40 cm 2 cm −3 as the order of magnitude for the present study. 18 Thus, the geometric surface area of a piece of nickel foam electrode can be calculated by the following equation:…”
Section: Methodsmentioning
confidence: 99%
“…In 2019, Zhang et al [66] reported a record activity value for the diyne-linked triethnylbenzene polymer 12 as nanofibers formed in situ on a Cu foam substrate, namely 1.09 mA cm −2 , which is more than 100-times greater than the previously reported values at 0 V versus RHE when irradiated under 1-sun conditions. (Specific surface area of the Cu foam is >10 2 cm 2 cm −3 , [67] the reported current density per the cathode flat surface could be re-estimated).…”
Section: Light-enhanced Hydrogen Production With π-Conjugated Polymers: Early Trials Using Conventional Polymers and High-performing Desimentioning
confidence: 97%
“…Further, the knowledge of the porosity and the pore size distribution allows for the estimation of the specific surface area as demonstrated in Refs. [84,85]. The total length of the borders and the area of the solid phase were calculated within COMSOL Multiphysics® 5.5 and when these two quantities are divided, the specific surface area is obtained for the investigated slice.…”
Section: Specific Surface Areamentioning
confidence: 99%